Communicating the green agenda a study on the origins and source of the environment as a social problem and the treatment of the Philippine Daily Inquirer and the Philippine Star of environmental stories - De Belen, Janice Ruth S.
This thesis is a study on the origins and source of environmental stories and the treatment of the Philippine Daily Inquirer and the Philippine Star of these stories. All environmental stories published in the main section of the Inquirer and the Star for the year 1999 were content analyzed. The main variables used in this research were the two broadsheeets' treatment of environmental stories and the news fora and sources of information of these articles. Treatment was measured through an analysis of the specific topics, whether these environmental stories focused on pollution, natural resources exploitation, natural disasters of La Niña and El Niño phenomena. These were then compared in terms of the type and slant, and the attention and emphasis given to the environmental stories. Findings revealed that the Inquirer had the most number of stories about pollution, while stories about environmental politics were fewest. Philippine Star, on the other hand, had also the most number of stories on pollution, while stories about development projects were fewest. Both newspapers newspapers had no stories about ozone depletion of global warming. Both the Inquirer and the Star had more environmental stories written in straight news form, than feature, investigative and interpretative stories combined. Most articles in the Inquirer had an unfavorable slant, while in the Star, most articles had a neutral slant. Results also showed the Inquirer leading the Star in terms of the attention and emphasis given to the environmental stories. The Inquirer also had bigger heads for its environmental stories and more articles with bigger accompanying visuals. This means that the Inquirer reported more extensively on environmental issues and gave greater prominence to environmental stories. In terms of news forum, the government was the main cause of coverage for the stories published in the two broadsheets. The less prominent fora include foreign government action/statement, courts/legal proceedings and individual personalities. Finally, in terms of the source of information, the Inquirer had more articles with non-affiliated citizens and individuals as their primary source of information, while the Star had more environmental stories coming from government officials and public authorities. This means that the Inquirer utilized non-official sources more in their environmental stories, while the Star tended to get the "official" viewpoint on matters concerning the environment.